Perancangan Sistem Aplikasi Antrian Apotek berbasis Web menggunakan Metode Agile - Bryan Farriq Reinaldy; hani sephani; Imam Wahyu Julianto; Zaisul Muttabi; Teti Desyani; Munawaroh Munawaroh (Teknik Informatika Universitas Pamulang, 2022)
The technology today is unavoidable to stop. One of the main areas in technology development is information technology. It becomes very inherent in everyday life at all ages. The website itself is an application that displays various kinds of views, aiming to share information so that users can use it easily and can also be reached properly. The word queue itself has a meaning, namely, where someone waits for each other's turn to get what he wants by waiting for his turn from others. The queue is usually someone who wants to do a service, but they have to wait because there are so many people. Limitation of the problem is carried out only includes the arrival rate, service time, queue discipline, and the number of service facilities available as well as the queuing process.Keywords: Information System, Queue, Website, MySQL